Cold Storage Increases Albumin and Advanced Glycation-End Product-Albumin Levels in Kidney Transplants: A Possible Cause for Exacerbated Renal Damage. Issue 6 (June 2019) - Lo, Sorena; Byrum, Stephanie D.; Tackett, Alan J.; Parajuli, Nirmala
Abstract : Background: Prolonged cold storage (CS) of kidneys is associated with poor renal outcome after transplantation (Tx). We recently showed that in rats (Lewis), proteasome and renal function were severely compromised in kidney transplants subjected to CS (CS/Tx) as compared with those without CS exposure (autotransplanted [ATx]). Methods: Evaluation of whole-kidney extracts from our rat kidney transplant model showed a subset of proteins induced after CS/Tx when compared with ATx or sham groups; this study examined those proteins using mass spectrometry, western blotting, immunoprecipitation, and immunohistochemistry. Results: Mass spectrometry identified basal albumin levels in sham kidney extracts; western blots and immunohistochemistry confirmed this. Western blotting showed exceptionally higher albumin levels in both soluble and insoluble fractions of CS/Tx renal extracts when compared with ATx and sham groups. Surprisingly, levels of advanced glycation-end products (AGE) were higher in CS/Tx renal extracts. Furthermore, immunoprecipitation of albumin followed by western blotting for AGE revealed AGE-albumin in all 3 extracts; its levels were highest in CS/Tx extracts. Immunohistochemistry analysis of kidney sections revealed higher albumin or AGE levels in the CS/Tx group, and the protein was detected all over (within glomeruli, and intratubular and extratubular compartments) when compared with ATx and sham groups, which show confinement of these proteins to the extratubular compartment and within glomeruli. As expected, kidneys of the ATx group showed evidence of more macrophages, which was exacerbated in the CS/Tx group. Conclusions: These results suggested that CS/Tx increased AGE-albumin, which was correlated with increased inflammation and renal damage.